GENES ASSOCIATED WITH BLOOD PRESSURE TRAITS SHOW CELL TYPE-SPECIFIC EXPRESSION AND CONTROL MULTIPLE CAUSAL LINKS TO BLOOD PRESSURE REGULATION IN THE HUMAN KIDNEY. (April 2021) - Eales, James; Jiang, Xiao; Xu, Xiaoguang; Saluja, Sushant; Cano-Gamez, Eddie; Pramanik, Sanjeev; Bogdanski, Pawel; Wystrychowski, Wojciech; Zywiec, Joanna; Zukowska-Szczechowska, Ewa; Woolf, Adrian; Maffia, Pasquale; et al.
Abstract : Objective: Hypertension affects 35% of the global adult population. It is a major risk factor for stroke, heart failure and coronary artery disease and is the leading preventable risk factor for premature death globally. Here we describe our approach to determine the causal pathways between genetic variants and blood pressure through the expression of kidney genes. Design and method: We used a catalogue of all known blood pressure associated genetic variants, gene expression profiles from 430 human kidney tissue samples and a single-cell gene expression data set to identify causal relationships with blood pressure using a colocalisation analysis and an ensemble of Mendelian randomisation methods. Results: By combining genome-wide genotypes and gene expression profiles from RNA-sequencing in an expression quantitative trait loci (eQTL) analysis we identify 418 genes where expression is modified by genetic variants previously associated with blood pressure traits. To investigate how these genes are expressed in the kidney we used gene expression profiles from 41, 778 human renal cells and identified 390 (93%) of these genes to be expressed in these cells with 69 (18%) showing expression specific to individual renal cell types. There was a statistically significant enrichment for expression of blood pressure associated genes in juxtaglomerular cells and cells from the collecting tubule. We identified 111 genes where the eQTL and blood pressure association colocalised and then applied an ensemble of Mendelian randomisation (MR) methods to determine which genes also have a causal effect on blood pressure in the kidney. Our MR analysis identified 53 (13%) genes where expression is causally linked to blood pressure, these included: guanylate cyclase 1 (GUCY1A3), the main receptor for nitric oxide and the target of riociguat and nuclear receptor coactivator 7 (NCOA7) which regulates vacuolar proton pumping ATPase (V-ATPase) activity in the intercalated cells of the collecting duct. Conclusions: We have identified 53 kidney genes where expression is causally linked to blood pressure. This not only highlights the importance of the kidney in blood pressure regulation, but also identifies putative targets for drug development or repurposing.